HUMOR AND SATIRE IN MARK TWAIN’S “THE ADVENTURE OF TOM SAWYER” NOVEL - Hidayat, Rahmat; Halim, Abdul; Syamsuddin, Muhammad Rifqi (Journal of English Literature and Linguistic Studies, 2024)
This research discusses the humor and satire that used by Mark Twain in “The Adventure of Tom Sawyer” novel. The aims of this study were (1) to identify Mark Twain’s humors that implied in The Adventure of Tom Sawyer, (2) to find out what types of satire that Mark Twain’s use reflected in The Adventure of Tom Sawyer, and (3) to find out the context of humor and satire that Mark Twain used in his work. This research used a qualitative descriptive method by collecting data from the utterances by each character of The Adventure of Tom Sawyer. The researcher used Martin’s theory about types of humor and Abram’s theory about types of satire. Based on the data that has been collected and analyzed, it shows that there are 3 types of humor used by Mark Twain in his work that is Jokes, Spontaneous Conversational Humor, and Unintentional Humor. Then, it also found Horatian type of satire in Twain’s work. Mark Twain used Cultural Context when he used types of satire.